Feasibility of Mangrove Forest Products as Fabric Natural Dyes in Garut Regency - Setiajiati, Fitta; Syalsyabila, Shyfa; Pribadi, Hendri; Poetra, Rakha Aditya; Fauziah, Ilya; Novitasari, Sukma (P4W IPB, 2023)
Mangrove forests have tangible and intangible benefits, but mangrove deforestation and degradation in Indonesia are relatively high due to economic reasons. Mangroves can contribute economically by considering social and economic characteristics, such as natural dye on traditional fabrics. Unfortunately, studies on mangroves' potential as a natural fabric dye and their relationship with social and economic potential are limited. Therefore, this study aimed to analyze the feasibility, prospects, and challenges in developing natural dyes from mangroves for traditional fabrics. Through field observations in the Leuweung Sancang Nature Reserve in Garut Regency, interviews, and literature studies, this study used a descriptive approach with SWOT and financial analysis. At least three mangrove species can be used as natural dyes to produce brown color variants: Bruguiera gymnorrizha, Rhizophora mucronata, and Rhizophora apiculata. The strategic location, with an intense fabric industry and high community motivation, provided opportunities to develop mangrove dye products. The business was feasible and resistant to the economic crisis. However, even though the community knows the mangrove benefits of natural fabric dyes, there was no development practice because of no assistance in processing. Supports from the government, forestry extension agents, NGOs, and universities are essential for mangrove conservation while improving livelihood and economic welfare through the mangrove natural dyes business.